The Influence of Celebrity Endorser Variables on Brand Image - Triana Prihatinta; Srimiatun; Rino Desanto Wiwoho; Clarista Bunga Rahmadhani; Elia Andi Ranigiyan (MultiTech Publisher, 2023)
This research aims to determine the effect of Celebrity Endorser Variables on Brand Image (Study on Skintific Product Users in Madiun City). The population in this study were all consumers of Skintific products in Madiun City. The research sample is part of the consumers of Skintific products in Madiun City, totaling 100 people. Data was obtained using a questionnaire. The sampling technique in this study used probability sampling and simple random sampling methods. Hypothesis testing using multiple linear regression analysis with the help of the SPSS 22 program. The result obtained is that the existence of Celebrity Endorsers will build or maintain Brand Image to customers. So the better a public figure in becoming a telada, the higher the Brand Image in the eyes of customers.